E-Marketing and Survival of Micro, Small and Medium Enterprises (MSMEs) in Uganda, A Study of Northern Uganda (International Journal of Management and Sustainability, 2015)
This study examined the relationship between e-marketing and Survival of Micro Small and Medium Enterprises (MSMEs) in Uganda, with particular emphasis to Northern Uganda. The study objectives were; to examine the relationship between e-marketing and MSMEs survival, to analyze the effect of different e-marketing services on MSMEs survival, investigate the effect of e-marketing performance on MSMEs survival and to determine the moderating effect of marketing innovations on the relationship between e-marketing and MSMEs survival. The study was based on the frequent media reports and the researcher’s experience over low survival rate of MSMEs. Several reports indicated that MSMEs in Northern Uganda do not live to see their first birthday and for almost every 35% of the MSMEs that close, about 37% start new businesses again. The study used a cross sectional descriptive design where both qualitative and quantitative methods were employed. A total of 175 respondents were sampled from a population of 322 including Micro, small and Medium Enterprises owners, Managers and District officials. Using a combination of self-administered questionnaires and interview guides for District officials, results shows that there is perfect relationship between e-marketing and MSMEs survival. The findings also indicate that different e-marketing services affect MSMEs survival significantly. Further, the study indicated that e-marketing performance affects MSMEs survival greatly. The study concludes that marketing innovations acts as an important moderator in the relationship between e-marketing and MSMEs survival. The study recommended that MSMEs owners and Managers should increase the use of e-marketing services in their enterprises to enable them survive and be competitive. This can be done through business website development, frequent internet use, social network, computer use, and Search engine optimization. The researcher also recommended that MSMEs owners / Managers should not overuse word of mouth in their businesses as it does not promote business survival. Word of mouth should only be used in few situations, when it is absolutely imperative, such situations can be where customers are illiterate of e-marketing services. MSMEs owners and Managers were also advised to properly train in e-marketing services and be committed in using what they have learnt so as to encourage their customers in using e-marketing.